PENGARUH LATIHAN SPRINT DAN ZIG-ZAG RUN TERHADAP PENINGKATAN KECEPATAN PADA PESERTA EKSTRAKURIKULER FUTSAL PUTRI SMP NEGERI 4 SURADE - Famelia Asy'ari, Ajeng; Hadi Hambali, Asep; Toriq, Ahmad; Nurjaman, Bela; Hikmat, Lukmannul; Rohman, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Speed is one of the most essential physical components required in futsal because players must perform rapid acceleration, directional changes, pressing, and transitions during the game. Based on preliminary observations, the speed performance of female futsal extracurricular participants at SMP Negeri 4 Surade was still below expectations. This study aimed to determine the effect of Sprint and Zig-zag Run training on improving players' speed. The study employed a quantitative approach using a pre-experimental method with a One Group Pretest–Posttest Design. The participants consisted of 16 female futsal extracurricular students selected using total sampling. Speed was measured using the 30-meter Sprint test. Data were analyzed using descriptive statistics, normality tests, residual normality tests, and paired sample t-test with SPSS version 25 at a significance level of 0.05. The findings revealed a significant improvement in participants' speed after receiving Sprint and Zig-zag Run training, as indicated by a significance value of 0.000 (p<0.05). Therefore, Sprint and Zig-zag Run training can be implemented as an effective physical training program to improve the speed of female futsal players in school extracurricular activities.